The Use of Dixit Board Game to Develop EFL Students’ Speaking Skills - Fathira Qalbina; Rofiqoh Rofiqoh; Zarkiani Hasyim; Konder Manurung (Hasanuddin University, 2025)
Many (EFL) frequently encounter difficulties in developing their speaking abilities, frequently because of restricted chances for practice and the lack of of interactive activities in the classroom. This research aimed to evaluate the effectiveness of the Dixit board game in enhancing the speaking abilities of eleventh-grade students at SMA Negeri 9 Palu through a quasi-experimental design. The study included two groups: class XI MIA 2, which acted as the experimental group, and class XI MIA 1, which served as the control group, both selected through purposive sampling. A speaking test was employed as the research instrument, focusing on three main criteria: fluency, accuracy, and comprehensibility. Both groups underwent a pre-test and a post-test, with the experimental group participating in six treatment sessions using the Dixit board game. Data analysis was conducted using SPSS version 25. The results indicated that the average score of the experimental group increased from 54.46 to 76.46, while the control group’s score rose from 49.10 to 59.20. The Shapiro-Wilk test confirmed normal distribution of the data, and Levene’s Test indicated equal variances (p = 0.610 > 0.05). A paired sample t-test demonstrated a significant improvement in the experimental group (p = 0.000 < 0.05), and an independent sample t-test revealed a significant difference in post-test scores between the two groups (p = 0.000 < 0.05). These findings suggest that utilizing the Dixit board game significantly enhances students’ speaking skills and supports its use as an interactive and student-centered tool in EFL speaking instruction.